2018
DOI: 10.1111/vsu.12949
|View full text |Cite
|
Sign up to set email alerts
|

Management of total hip replacement luxation with triple pelvic osteotomy

Abstract: Objective To report the outcome of dogs treated with triple pelvic osteotomy (TPO) for dorsal luxation after total hip replacement (THR). Study design Retrospective clinical case series. Animals Seventeen client‐owned animals. Methods Medical records were searched at a single institution for dogs that had been treated with TPO for dorsal THR luxation. The angle of lateral opening (ALO), version angle (VA), and inclination angle (IA) were measured from radiographs after THR and TPO and corrected for pelvic rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…Our first hypothesis was confirmed: DPO's median decrease in ALO obtained in this study was 11°. This was lower than the mean value of 23° obtained by TPO in another study 12 . Two main factors may explain this difference in ALO reduction between the two studies.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Our first hypothesis was confirmed: DPO's median decrease in ALO obtained in this study was 11°. This was lower than the mean value of 23° obtained by TPO in another study 12 . Two main factors may explain this difference in ALO reduction between the two studies.…”
Section: Discussioncontrasting
confidence: 70%
“…It could be assumed that the ALO recommended values were insufficient to eliminate the risk of luxation. After TPO, cases of recurrence of THR luxation have been reported, particularly ventral luxation (3/18 cases) 12 . These complications were attributed to impingement between the cup and the stem; this was related to the decrease in ALO with an increase in VA and inclination angle (IA) or even an excessive decrease in ALO 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 , 20 Most other published studies to date on canine THR have also only reported cases from a single center. 26 , 27 , 28 , 29 …”
Section: Introductionmentioning
confidence: 99%